REKONSTRUKSI BASIS PERHITUNGAN KERUGIAN NEGARA DALAM PERISTIWA TINDAK PIDANA KORUPSI PADA SEKTOR SUMBER DAYA ALAM - Muhamad Muhdar (Fakultas Hukum Universitas Balikpapan, 2020)
This article aims to examine: First, how to determine calculation basis of state loss in the event of corruption in natural resource sector. Second, whether environmental destruction and pollution resulting in the loss or the degradation of economic value of the environmental can be the basis to extend the meaning of state loss. The constitution declares that the natural resources are under the power of the state. This constitutional right means that the state is authorized to control state resources. The state rule over natural resources is confirmed by state rights to manage, distribute as well as protect the utilization in order to be useful for social well-being. However, it is argued that the state is not without blemish in term of effective management as destruction and pollution are rampant. Furthermore, natural resource utilizers and certain people in the state agencies commit crime in concert in various sectors of natural resources. State loss in term of financial obligation value or contractual relationship is barely able to dismiss the weakness on the part of the state in protecting the common goods. It is therefore necessary to extend state loss calculation by adding the degradation or the loss of state income and the increasing public burden as a result of the destruction of livelihood.